Potency of the Combination of Chitosan and Hydroxyapatite on Angiogenesis and Fibroblast Cell Proliferation in Direct Pulp Capping of Rattus norvegicus - Sularsih, Sularsih; Fransiska, Wanli; Salsabila, Syifa; Rahmitasari, Fitria; Soesilo, Diana; Prananingrum, Widyasri (European Journal of Dentistry, 2024)
Objectives The aim of this research was to analyze expression of vascular endothelial growth factor (VEGF), blood vessels, and fibroblast cell proliferation in direct pulp capping treatment of Rattus norvegicus using a combination of chitosan and hydroxyapatite paste.Materials and Methods The samples were male R. norvegicus strains of Wistar rats, weighing 200 to 250 g and aged between 8 and 16 weeks. The occlusal surface of the molars of R. norvegicus was prepared with class I cavity and then perforated with the tip of an explorer. Sixty male R. Norvegicus rats were divided into the following: control group (KA) in which the cavity was filled with glass ionomer cement; control group (KB), in which the cavity was filled with Ca(OH)2; PA group, in which the cavity was filled with chitosan (CH); PB group, in which the cavity was filled with hydroxyapatite (HA); and PC group, in which the cavity was filled with chitosan and hydroxyapatite (CH-HA). Each group was divided into 3-, 7-, and 14-day observation groups. The mandibular bone of the molar was cut and histopathological examination was performed to analyze the blood vessels and fibroblast cell proliferation. Immunohistochemistry examination was done to examine the expression of VEGF.Statistical Analysis The data variation was analyzed with One Way Analysis of Variance (ANOVA) test and continued with multiple comparison Least Significant (LSD) test to determine the different pairs of group.Results Analysis of variance (ANOVA) showed a significant increase in the expression of VEGF, blood vessels, and fibroblast cell proliferations (p ≤ 0.05;), especially in the PC group compared to the other four groups. The least significant test (LSD) test showed significant differences between the groups on the expression of VEGF, blood vessels, and fibroblast cell proliferations.Conclusion The combination of chitosan and hydroxyapatite could promote healing of direct pulp capping treatment by increasing the expression of VEGF, blood vessel, and fibroblast cell proliferation.
Keywords: chitosan; hydroxyapatite; direct pulp capping; VEGF; blood vessel; fibroblast